Mu‘tazilah and the Modernization of the Indonesian Muslim Community: Intellectual Portrait of Harun Nasution - Mujani, Saiful (Studia Islamika, 1994)
Harun Nasution was born on 23rd September 1919 in Southern Tapanuli, North Sumatra and came from an elite family of his region. HIs father, Abdul Jabbar Ahmad, went on a pilgrimage to Mecca when he was very young. When he grew up he become successful trader, or more precisely an importer of some commodities from Singapore. It was a rare phenomenon in a colonial times for an Indonesian native to become a successful trader.DOI: 10.15408/sdi.v1i1.868